2017
DOI: 10.1116/1.4987131
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-enhanced atomic layer deposition of vanadium phosphate as a lithium-ion battery electrode material

Abstract: Vanadium phosphate films were deposited by a new process consisting of sequential exposures to trimethyl phosphate (TMP) plasma, O 2 plasma, and either vanadium oxytriisopropoxide [VTIP, OV(O-i-Pr) 3 ] or tetrakisethylmethylamido vanadium [TEMAV, V(NEtMe) 4 ] as the vanadium precursor. At a substrate temperature of 300 C, the decomposition behavior of these precursors could not be neglected; while VTIP decomposed and thus yielded a plasma-enhanced chemical vapor deposition process, the author found that the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Both materials exhibit a good coulombic efficiency with a decent, but not ideal, cycle life (where approximately 89% of the capacity is retained after 50 cycles for both phosphates). The capacity retention is slightly worse compared to other metal phosphates deposited through a similar ALD process, 22,23,25 which is thought to originate from the nature of the electrochemical reactions. While the previously reported metal phosphates relied on intercalation-type reactions, the conversion or alloying reactions that might take place in the nickel and cobalt phosphate could lead to a slightly less stable cycle life.…”
Section: Papermentioning
confidence: 90%
See 1 more Smart Citation
“…Both materials exhibit a good coulombic efficiency with a decent, but not ideal, cycle life (where approximately 89% of the capacity is retained after 50 cycles for both phosphates). The capacity retention is slightly worse compared to other metal phosphates deposited through a similar ALD process, 22,23,25 which is thought to originate from the nature of the electrochemical reactions. While the previously reported metal phosphates relied on intercalation-type reactions, the conversion or alloying reactions that might take place in the nickel and cobalt phosphate could lead to a slightly less stable cycle life.…”
Section: Papermentioning
confidence: 90%
“…In this work, an initial attempt towards researching ALD of nickel phosphate will be made based on earlier work by Dobbelaere et al 21 In this work, aluminium phosphate was deposited through a plasma-enhanced ALD process (PE-ALD), combining trimethylphosphate plasma (TMP*, with the star denoting the plasma state) with oxygen plasma and trimethylaluminum (TMA). However, it was quickly found that by changing the metal precursor, other metal phosphates such as titanium, 22 vanadium, 23 zinc, 24 iron 25 and cobalt phosphates 26 could be deposited as well. For the deposition of nickel phosphate in this work, the metal-organic precursor of choice became nickelocene, inspired by our earlier work on PE-ALD of cobalt phosphate and as this precursor has already proven to be successful towards PE-ALD of nickel oxide.…”
Section: Introductionmentioning
confidence: 99%
“…For example, T. Dobbelaere et al developed an ALD process for vanadium phosphate on flat substrates involving O 2 plasma. 1 In fact, plasma has the drawback of surface recombination and might not be suitable for ALD on powders, especially in fixed bed geometry or with porous powders. 27,28 Therefore, surface modification of existing bulk catalysts is in some cases the only option to obtain the desired surface layer.…”
Section: Introductionmentioning
confidence: 99%
“…5 times higher than for typical ALD. By changing the metal precursor at the end of each cycle, the approach could be extended to titanium 16 , vanadium 25 , zinc 26 , iron 17 and cobalt phosphate 27 .…”
Section: Introductionmentioning
confidence: 99%